(untitled) (ENTHYMEMA, 2020)
This paper intentionally crosses Italian poetry from the Seventies to the present day in a partial, oblique and non-panoramic way, privileging still open questions, experiences at risk of being forgotten or penalized, and connections between authors no longer or not yet valued. The purpose of the essay is not to draw a new and organic historical and literary panorama, rather it aims to reopen some discussion points and is therefore critically focused on specific thematic and stylistic issues.